Drop-Shipping – A Business Model Without Holding Inventory: A Case Study of Online Store - Cristian BARCS; Izabela Luiza POP; Cezar TOADER; Diana IGHIAN (Communications of International Proceedings, 2022)
Drop-shipping is a recently new, commonly used fulfilment method, especially in e-commerce sites. By applying drop-shipping, many businesses and e-commerce sites have the possibility to reach a much greater customer base, as well as manage their business without holding, in most cases, any product as stock. This order fulfilment method has made possible the existence of drop-shipping as a business model, people from all over the world being able to sell items internationally, without ever seeing them. Also, the start-up cost for such a business is rather low, since there is no need for deposit means, a physical store, or even employees. However, the low barrier of entry this business model determines many people to try it, which is why the competition is very high. Even though the business looks easy, the low barrier of entry and the great competition means that only a small fraction of the new drop-shipping businesses get profitable. This paper will analyze what are the odds of turning such a business profitable while also looking at which are the pillars of drop shipping and most importantly, how the people who succeed are doing it. The proposed theoretical model is illustrated through a case study conducted at a drop-shipping store that is selling back posture correctors. The results of the study are useful both, for practitioners and scholars interested in the topic of drop-shipping.
Keywords: drop-shipping; e-commerce; business; management